Development of a crawler chassis attitude adjustment device for a self-propelled maize harvester and experiment of fuselage leveling - Tan, Hewen; Wang, Gang; Zhou, Shuhui; Jia, Honglei; Zou, Zhaobo; Qu, Minghao (International Journal of Agricultural and Biological Engineering, 2024)
Self-propelled maize harvesters are prone to overturning when operating on sloping ground. Solving this problem presents a major technical challenge for researchers. Existing under carriage leveling technologies are mostly single leveling mechanisms and have a small adjustable angle. A chassis attitude adjustment device has been developed to increase the flexibility of the harvester to slope terrain. The device is made up of a double leveling mechanism and a leveling control system, and it is used to regulate the lateral and longitudinal attitude of the harvester while it is operating. To maintain the attitude of the fuselage within the desired range, the leveling control system regulates the amount of hydraulic cylinder expansion and contraction. The kinematic analysis of the leveling mechanism was done using the vector approach, and the device can be adjusted for lateral and longitudinal inclination between –10° and 17°, and –43.1° and 43.1°, respectively. According to the findings of the static tests, the chassis attitude adjustment device can level the fuselage in four tilt attitudes -10° uphill, 17° downhill, 25° sideways slope forward, and 25° sideways slope return - with a maximum leveling error of 0.37°and the fastest leveling rate of 0.233 s/(°). For the purpose of evaluating the chassis attitude adjustment performance in the field tests, the tilt inclination of the fuselage was selected as an assessment indicator. The body tilt of the harvester ranged from 0.13° to 1.81° at a harvester speed of 2.5 km/h, with an average body tilt angle of 0.78°, showing that the under carriage attitude adjustment system was capable of actively leveling the maize harvester attitude. This study enabled the dynamic equilibrium for the maize harvester, which can act as an upstream technology for the design of slope travel devices.Keywords: crawler harvesters, adjustment mechanism, leveling control systems, vectors methodDOI: 10.25165/j.ijabe.20241706.8551Citation: Tan H W, Wang G, Zhou S H, Jia H L, Zou Z B, Qu M H. Development of a crawler chassis attitude adjustmentdevice for a self-propelled maize harvester and experiment of fuselage leveling. Int J Agric & Biol Eng, 2024; 17(6): 111–120.